Technology Integration in English Learning in East Kalimantan - Rostanti Toba; Susanto Susanto (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2018)
This study aims to identify forms of technology integration in learning English at MTs. level, especially in the East Kalimantan region, and to find out the forms of learning innovations carried out by English teachers as a form of solution to the challenge of the science and technology development in the digital era. This type of research is qualitative descriptive, and observations, interviews, and documentation as a form of data collection techniques, then analyzed based on Miles and Huberman's theory with the stages of initial observation, data collection research, data reduction, data compilation and grouping, validation, and conclusions. The results obtained are the types of technology used in learning English including Youtube, WhatsApp, email, blog, Facebook, Instagram, and Twitter. The form of learning innovations conducted by teachers is based on the use of technology that is utilized in the form of innovative strategies, methods, techniques, design of teaching materials, and development of teaching materials.